PEMIKIRAN PENDIDIKAN ABDURRAHMAN SALEH ABDULLAH (Resensi Buku â€œTeori-teori Pendidikan Berdasarkan Al-Quranâ€) - Muhammad Tang. S (AZKIYA, 2018)
The objectives of education, materials and methods of pangajaran in Islam have been discussed in the Qur'an. The basics regarding practical issues are essential issues in order to achieve the desired goals. This essay is in the form of a review of Abdurrahman Saleh Abdullah's work entitled: "Teori-Teori Pendidikan Berdasarkan Alquran" published by Rineka Cipta Publishers, Jakarta, in 1990. His paper gives an overview of the challenges for all Muslims in general and educators at in particular, to critically analyze accepted educational practices. Discussion of this paper is done on matters relating practically to the world of education, namely on the purpose of Islamic education, Islamic education materials and methods of Islamic education.